MODEL PENDIDIKAN BERBASIS QUDWAH HASANAH: TELAAH TAFSIR SYAIKH MUTAWALLI SYA’RAWI ATAS SURAT AL-FATH [29] - Aiena Rissa Fadlilatulaila; Muchlis Zaidan; Dzulkifli Hadi Imawan (STKIP Subang, 2026)
This study focuses on analyzing Syaikh Mutawalli Sya’rawi’s interpretation of Surah Al-Fath verse 29, which portrays Prophet Muhammad (peace be upon him) and his companions as Qudwah Hasanah exemplary role models. Syaikh Sya’rawi, a contemporary Egyptian scholar, is renowned for his distinctive exegetical style that combines linguistic depth, communicative clarity, and relevance to contemporary social issues. The urgency of this research arises from the current crisis of moral exemplarity within educational settings, emphasizing the importance of reintroducing the Prophet’s values of Qudwah into modern education. The primary aim of this study is to explore Syaikh Sya’rawi’s understanding of the Prophet’s and companions’ exemplary qualities and to examine their relevance to character formation in today’s educational context. This research employs a qualitative method using a literature review approach, with the data analyzed descriptively. The findings reveal that, according to Syaikh Sya’rawi, the values of Qudwah Hasanah embodied by the Prophet and his companions include firmness in upholding the faith, compassion toward others, and complete obedience to Allah Almighty. These values remain highly relevant to modern education as a means to revive the presence of authentic role models who can inspire the younger generation.